Role of Patient Feedback in Better Medical Care - Slehria, Atiq ur Rehman (Pakistan Armed Forces Medical Journal, 2023)
Patient satisfaction and experience are important indicators for measuring healthcare quality. The recent widespread use of patientexperience surveys in healthcare settings is based on the fact that feedback has a potentially important role in improving the quality of care, affects clinical outcomes and timely, efficient, patient-centred delivery of quality health. Research into patient experience feedback is a relatively recent phenomenon that began in the 1990s.1 Research into how healthcare providers use this data to improve services is at an early stage. Recent systematic research on patient experience and feedback collection was held at the Armed Forces Institute of Radiology & Imaging (AFIRI), providing evidence to influence debate, policy and practice on patient feedback data.